ChemInform Abstract: Azabicycles Construction: The Transannular Ring Contraction with N‐Protected Nucleophiles. Issue 40 (30th September 2014) - Rizzo, Antonio; Harutyunyan, Syuzanna R.
Abstract Review: [54 refs.